2022
DOI: 10.48550/arxiv.2201.13211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Three-dimensional AdS black holes in massive-power-Maxwell theory

Abstract: Recently, it was shown that power-Maxwell (PM) theory can remove the singularity of electric field [1]. Motivated by great interest in three-dimensional black holes and a surge of success in studying massive gravity from both the cosmological and astrophysical point of view, we investigate such black hole solutions in de Rham, Gabadadze and Tolley (dRGT) massive theory of gravity in the presence of PM electrodynamics. First, we extract exact three-dimensional solutions in the PM-dRGT massive gravity. Then we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 137 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…This is to be contrasted to what happens in the case of the standard Reissner-Nordström solution [48]. Finally, a toy model that generalizes Maxwell's theory in a straightforward manner leads to the so called Einstein-power-Maxwell (EpM) theory [49][50][51][52][53][54][55][56][57][58][59][60][61][62], described by a Lagrangian density of the form L(F ) ∼ F k , where F is the Maxwell invariant, and k is an arbitrary rational number. One of the advantages of EpM theory is that the nice conformal properties of the four-dimensional Maxwell's theory are preserved in any number of space-time dimensionality D, provided that the power k is chosen to be k = D/4, as it is easy to verify that for this particular value the electromagnetic stress-energy tensor becomes traceless.…”
Section: Introductionmentioning
confidence: 99%
“…This is to be contrasted to what happens in the case of the standard Reissner-Nordström solution [48]. Finally, a toy model that generalizes Maxwell's theory in a straightforward manner leads to the so called Einstein-power-Maxwell (EpM) theory [49][50][51][52][53][54][55][56][57][58][59][60][61][62], described by a Lagrangian density of the form L(F ) ∼ F k , where F is the Maxwell invariant, and k is an arbitrary rational number. One of the advantages of EpM theory is that the nice conformal properties of the four-dimensional Maxwell's theory are preserved in any number of space-time dimensionality D, provided that the power k is chosen to be k = D/4, as it is easy to verify that for this particular value the electromagnetic stress-energy tensor becomes traceless.…”
Section: Introductionmentioning
confidence: 99%
“…By considering this theory of massive gravity, many works were done. For example, black hole solutions and their thermodynamic properties are investigated in [31][32][33][34][35][36][37][38][39][40]. It was shown that there is a correspondence between black hole solutions of conformal and this theory of massive gravity [41].…”
Section: Introductionmentioning
confidence: 99%